Faktor-Faktor Yang Mempengaruhi Kejadian Covid-19 Di Desa Sutera - Tamara, Arswendy Okky; Saepudin, Malik; Wardoyo, Slamet; Martini, Martini (Jurnal Riset Kesehatan Masyarakat, 2024)
Coronavirus is an RNA virus that typically causes respiratory disease in humans.  It is known that the total number of cases in Wuhan is 50,340. Prevention of the spread of Covid-19 is closely related to the implementation of health protocols. The purpose of the study was to determine the factors that influence the incidence of Covid-19 in Sutera Village. This research method is an observational study research design with the selection of unmatched case-control subjects. The sample in this study amounted to 156 samples consisting of 104 cases and 52 controls from Sutera Village. The results of this study indicate that there is a relationship between knowledge and the incidence of Covid-19 (p = 0.044; OR = 4,455), attitudes and the incidence of Covid-19 (p = 0.037; OR = 4,500), age and the incidence of Covid-19 (p = 0.035; OR=4,455), education with the incidence of Covid-19 (p=0,027; OR=1,624), health facilities with the incidence of Covid-19 (p=0,031; OR=0,205), and prevention efforts with the incidence of Covid-19 (p=0,022; OR=5,308). Based on these results, it is necessary to hold outreach activities to increase the role of the community and provide better services in the effort to prevent Covid-19.